A Proposed Concept for Defective Mitophagy Leading to Late Stage Ineffective Erythropoiesis in Pyruvate Kinase Deficiency - van Vuren, Annelies Johanna; van Beers, Eduard Johannes; van Wijk, Richard (Frontiers in Physiology, 2021)
Pyruvate kinase deficiency (PKD) is a rare congenital hemolytic anemia caused by mutations in the PKLR gene. Here, we review pathophysiological aspects of PKD, focusing on the interplay between PK-activity and reticulocyte maturation in the light of ferroptosis, an iron-dependent process of regulated cell death, and in particular it’s key player glutathione peroxidase 4 (GPX4). GPX4 plays an important role in mitophagy, the key step of peripheral reticulocyte maturation and GPX4 deficiency in reticulocytes results in a failure to fully mature. Mitophagy depends on lipid oxidation which is under physiological conditions controlled by GPX4. Lack of GPX4 leads to uncontrolled auto-oxidation which will disrupt autophagosome maturation and thereby perturb mitophagy. Based on our review, we propose a model for disturbed red cell maturation in PKD. A relative GPX4 deficiency occurs due to glutathione depletion, as cytosolic L-glutamine is preferentially used in the form of α-ketoglutarate as fuel for the tricarboxylic acid cycle at the expense of glutathione production. The relative GPX4 deficiency will perturb mitophagy and, subsequently, results in failure of reticulocyte maturation, which can be defined as late stage ineffective erythropoiesis. Our hypothesis provides a starting point for future research into new therapeutic possibilities which have the ability to correct the oxidative imbalance due to lack of GPX4.